2013
DOI: 10.1186/scrt195
|View full text |Cite
|
Sign up to set email alerts
|

The dual effect of mesenchymal stem cells on tumour growth and tumour angiogenesis

Abstract: IntroductionUnderstanding the multiple biological functions played by human mesenchymal stem cells (hMSCs) as well as their development as therapeutics in regenerative medicine or in cancer treatment are major fields of research. Indeed, it has been established that hMSCs play a central role in the pathogenesis and progression of tumours, but their impact on tumour growth remains controversial.MethodsIn this study, we investigated the influence of hMSCs on the growth of pre-established tumours. We engrafted nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 57 publications
4
25
0
1
Order By: Relevance
“…For example, Kaposi sarcoma tumours in mice were growth inhibited by around two thirds via inactivation of Akt-mediated pathways in the presence of MSCs [28] and murine hepatoma and lymphoma cell line growth was reduced by up to 90% in vitro and in vivo [29]. Similar results were found using lung cancer cell line A549 and metastasis was also inhibited [30,31]. MSCs have also been shown to decrease breast cancer cell migration and invasion via production of the tissue inhibitors of matrix metalloproteinases TIMP-1 [32] and TIMP-2 [33].…”
Section: The Role Of Mscs In Cancer Development and Progressionsupporting
confidence: 72%
“…For example, Kaposi sarcoma tumours in mice were growth inhibited by around two thirds via inactivation of Akt-mediated pathways in the presence of MSCs [28] and murine hepatoma and lymphoma cell line growth was reduced by up to 90% in vitro and in vivo [29]. Similar results were found using lung cancer cell line A549 and metastasis was also inhibited [30,31]. MSCs have also been shown to decrease breast cancer cell migration and invasion via production of the tissue inhibitors of matrix metalloproteinases TIMP-1 [32] and TIMP-2 [33].…”
Section: The Role Of Mscs In Cancer Development and Progressionsupporting
confidence: 72%
“…The origins of MSCs should be taken into account when deciding the antitumor effect, as did in the case of hUC-MSCs which inhibit glioblastoma proliferation, but adipose tissue-derived not [26]. Considered the antitumor effect, human MSCs could be more interesting to use for the treatment of pre-established tumors [27]. We speculated that different tissue origin of MSCs, delivery methods, individual variations are key points for future MSCs mediated cancer therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent cells that exhibit a marked tropism for tumors [7, 8] and display controversial angiogenic properties: while some reports showed that MSCs support tumor angiogenesis [911], other studies observed a range of anti-angiogenic properties [1214]. This can be explained by many reasons, such as the complexity of the different MSCs origins and their specific properties on different cancer cell types [1517], as a consequence of the specific crosstalk between tumor cells, tumor microenvironment and MSCs, and by the MSCs-derived factors produced within the tumor [18].…”
Section: Introductionmentioning
confidence: 99%